Metformin Improves Epithelial-to-Mesenchymal Transition Induced by TGF-β1 in Renal Tubular Epithelial NRK-52E Cells via Inhibiting Egr-1. (27th June 2018) - Guan, Meiping; Li, Wenqi; Xu, Lingling; Zeng, Yanmei; Wang, Dan; Zheng, Zongji; Lyv, Fuping; Xue, Yaoming
Abstract : The early growth response- (Egr-) 1 has been found to play a key role in organ fibrosis. Metformin has been shown to be effective in attenuating renal tubular epithelial-to-mesenchymal transition (EMT), which is involved in renal fibrosis. However, it is unknown whether metformin improves EMT via inhibiting Egr-1. In this study, rat renal tubular epithelial (NRK-52 E) cells, treated by transforming growth factor- (TGF-) β 1 of 10 ng/ml with or without metformin of 1 mmol/l, were transfected by siEgr-1 or M61-Egr-1 plasmids to knock down or overexpress Egr-1, respectively. The gene and protein expressions of E-cadherin, α -SMA, fibronectin (FN), and Egr-1 were determined by real-time quantitative PCR and Western blotting, respectively. We observed that TGF- β 1 significantly reduced E-cadherin expression and upregulated the expressions of FN, α -SMA, and Egr-1, which can be reversed by metformin. M61-Egr-1 transfection could exacerbate EMT, which can be reversed by metformin. Taken together, our data show that Egr-1 plays an important role in TGF- β 1-induced EMT of renal tubular epithelial cells and metformin improves EMT while inhibiting Egr-1, which provides a potential novel target to combat renal fibrosis.